A blockchain-based code copyright management system. Issue 3 (May 2021) - Jing, Nan; Liu, Qi; Sugumaran, Vijayan
Highlights: The blockchain-based code copyright management system implements the verification, storage, and inquiry of code copyright. The copyright information stored in the blockchain is unique, accurate, and immutable, and can be queried based on the cryptography technology of blockchain. The system delivers an efficient and reliable verification approach for code copyright based on the consensus mechanism of blockchain. The copyright information is stored in decentralized nodes in the blockchain and thus protected from further tampering and embezzlement. Abstract: With the increasing number of open-source software projects, code plagiarism has become one of the threats to the software industry. However, current research on code copyright protection mostly focuses on the approach for code plagiarism detection, failing to fundamentally solve the problem of copyright confirmation and protection. This paper proposes a blockchain-based code copyright management system. Firstly, an Abstract Syntax Tree-based code originality verification model is constructed. The originality of the uploaded code is determined through its similarity to other original codes. Secondly, the Peer-to-Peer blockchain network is designed to store the copyright information of the original code. The nodes in the blockchain network can verify the originality of the code based on the code originality verification model. Then, through the construction of blocks and legitimacy validation and linking of blocks, the blockchain-based code copyright management structure is built. The whole process guarantees that the copyright information is traceable and will not be tampered with. According to the experiments, the accuracy and processing time of the code originality verification model are shown to meet code originality verification requirements. The experiment also shows that the best storage type of the code copyright information is the code fingerprint which is a 256bits hash value converted from code eigenvalues. It performs better in both response speed and storage efficiency. Moreover, because of the uniqueness and irreversibility of the result from the SHA256 algorithm, the code fingerprint storage yields a better level of storage security. In summary, this paper proposes a blockchain-based code copyright management system which provides better response speed and storage efficiency.